Autonomy in foreign language teacher education - Frodden, Cristina; Cardona, Gloria (Íkala, Revista de Lenguaje y Cultura, 2001)
This paper summarizes the findings of a research project conducted on the development of autonomy in foreign language teaching programs in two Colombian universities. This project can be seen as an outcome of an overall project (COFE Project), supported by the British and Colombian governments in which twenty-six other universities participated. The aim of the COFE project was to improve the quality of pre-service English language teaching programs (Licenciaturas) by qualifying teacher educators and promoting learner autonomy through the donation of resources centers.